The Mediating Effect of Model-Based Learning on Attitude and Pain Management Awareness Among Nurses During COVID 19 Pandemic in Saudi Arabia - Issa M.R.; Awanis Muslim N.; Mat Sharif Z. (SAGE Publications Inc., 2023)
Background: All hospitals are required to provide high-quality pain management; one of the most critical issues in achieving high-quality pain management is that the hospitals have a clear plan to manage the patients pain and improve the nurses awareness of pain management during the COVID 19 pandemic. However, there is a significant gap in the literature that this study can cover. Aim: This study aimed to investigate the mediating effect of model-based learning on nurses attitudes toward nurses pain management awareness during the COVID 19 pandemic in Saudi Arabia government hospitals. Method: The Heath Beliefs Model was used, with a quasi-experimental design, with per experimental one group pre-test post-test design, and a quantitative approach using self-administered questionnaires obtained from 330 nurses working with patients suffering from pain. IBM SPSS V23 and Analysis of Moment Structures (AMOS)V23 were applied to analyze the causal relationships between the variables. Results: A two-step approach to analyze the study: the first step was to test the measurement models constructs reliability and validity. The second step was to test research hypotheses in the structural models. The results show a significant positive relationship between model-based learning and pain management awareness among nurses during COVID 19 pandemic. Furthermore, model-based learning fully mediated the relationship between nurses attitudes and pain management awareness. Conclusions: The study successfully improved nurses attitudes toward pain management awareness among nurses during COVID 19 pandemic. These findings will help strengthen the debate in the existing literature, and this is a new development window in the pain management area. The Author(s) 2021.